Prevalência e caracterização da Síndrome das Pernas Inquietas/Doença de Willis-Ekbom em uma coorte de pacientes portadores de Doença Inflamatória Intestinal no Nordeste do Brasil - Borges, André Luis Pinheiro (2022)
Introduction: The inflammatory bowel disease IBD (Crohn's disease CD and ulcerative colitis RCU) is a chronic immunologically based pathology with predominant involvement in the digestive tract, but may also have extraintestinal manifestations. The restless legs syndrome/Willis Ekbom disease (RLS/WED) is a pathology of the central nervous system, which results in restlessness, especially in the lower limbs, predominantly at rest and at night, with repercussions on the quality of life of these patients, sleep and mood (anxiety and depression). Until recently neglected in patients with IBD, but which in recent years has been associated with IBD. In Brazil, there are no studies of RLS/WED in patients with IBD. General objective: To determine the prevalence and characterize RLS/WED in a cohort of patients with IBD. In addition, evaluate factors associated with RLS/WED, such as anthropometric data, anemia, vitamin B12 deficiency, diabetes, IBD activity, and the impact of RLS/WED on sleep and mood (anxiety and depression). Materials and Methods: The study was conducted in a cohort of IBD patients followed at the gastroenterology outpatient clinic of the HUWC. Previously validated questionnaires were applied for the diagnosis of RLS/WED, anxiety, depression and sleep. Epidemiological and demographic data, disease activity, blood count, vitamin B12 and glucose were collected. Patients with RLS/DWE based on the four criteria recommended for RLS/DWE and who did not belong to the exclusion criteria followed the neurological evaluation to exclude differential diagnoses. Results: A total of 210 patients were evaluated, initially 36 patients met the four criteria in the RLS/DWE questionnaire. We excluded 11 patients after neurological evaluation due to the exclusion criteria, 5 with polyneuropathy, 4 with fibromyalgia, and 2 did not understand the questionnaire. A total of 199 patients were included, 88 (44%) male and 111 (56%) female, 51.2% with UC (102/199), 48.7% with CD (97/199). The mean age of the patients was 44 years and the duration of IBD was 10 years. The prevalence of RLS/WED in general was 12.5% (n=25/199). Of these 25 patients, 10 (5.0%) were diabetic or prediabetic and 15 (7.5%) had no associated comorbidities, with CD 8.2% (8/97) and UC 6.8% (7/102). The RLS/WED was more prevalent in females 80% (20/25) versus 52.2% (91/174)) with a significant association even after logistic regression analysis (p = 0.003 OR:6.27; CI95% 2.08–23.9). There was no association with age, weight, height, alcoholism, diabetes, hypertension, anemia and vitamin B12 deficiency. RLS/DWE was significantly associated with anxiety p < 0.001 (68.0 %, (17/25)) versus 33.9 %, (59/174), this association was maintained even after logistic analysis (OR CI 95% 7.5 2.5-24.8 p=0.0001). In patients with CD, there was an association between moderate/severe disease activity. Most patients with IBD had poor sleep quality (score greater than or equal to 5) with no statistical difference between the group of patients with and without RLS/WED respectively 87.5% and 88.3%, however, the mean score was higher in the group with SIPDWE 11.0 ± 3.9 (12.0) versus 8.0 ± 3.2 (7.0) p <0.001. Conclusions: The prevalence of RLS/WED was similarly in patients with CD and UC. RLS/WED is associated with female gender, anxiety disorder and poorer sleep quality. IBD specialist should be aware of the symptoms of RLS/WED, being important to consult the neurologist for a definitive diagnosis. Further studies are needed to evaluate possible cofactors associated with RLS/WED.